Emergence and Collapse of Early Villages : Models of Central Mesa Verde Archaeology - Varien, Mark; Kohler, Timothy A. (Book collections on Project MUSE., 2012)
Comparing simulations from agent-based models with the precisely dated archaeological record from this area, this text will interest archaeologists working in the Southwest and in Neolithic studies as well as anyone applying modelling techniques to understanding how human societies shape, and are shaped by the environment.